Reformulation Of The Policy On The Placement Of Reclamation And Post-Mining Guarantee Funds Based On The Polluter Pays Principle - Amiruddin, A.M Adzkiya' (Supremasi Hukum: Jurnal Penelitian Hukum, 2025)
This study aims to describe and analyze the placement of reclamation and post-mining guarantee funds in mining activities. These funds serve as an economic instrument that compels license holders to carry out post-mining recovery. However, compliance among license holders in placing reclamation and post-mining guarantee funds remains problematic. In addition, this research seeks to analyze the reformulation of policies regarding the placement of reclamation and/or post-mining guarantee funds as an environmental economic instrument. The research method employed is normative juridical research with a descriptive analysis model. The findings show that after licenses are issued, many license holders fail to fulfill their obligation to place guarantee funds, resulting in disrupted environmental recovery activities. Under the prevailing regulations, the obligation to place reclamation and post-mining guarantee funds is imposed on IUP/IUPK holders after obtaining a license. With such a regulatory model, many IUP/IUPK holders neglect and fail to deposit the required funds. The current concept of placing reclamation and post-mining guarantee funds, which requires submission after license is issued by government, has led to non-compliance by license holders. Therefore, the concept of guarantee fund placement must be reformulated.